2012
DOI: 10.1007/s10071-012-0482-1
|View full text |Cite
|
Sign up to set email alerts
|

Delaying gratification for food and tokens in capuchin monkeys (Cebus apella) and chimpanzees (Pan troglodytes): when quantity is salient, symbolic stimuli do not improve performance

Abstract: Capuchin monkeys have been tested for the capacity to delay gratification for accumulating rewards in recent studies and have exhibited variable results. Meanwhile, chimpanzees have consistently excelled at this task. However, neither species have ever been tested at accumulating symbolic tokens instead of food items, even though previous reports indicate that tokens sometimes facilitate performance in other self-control tasks. Thus, in the present study, we tested capuchin monkeys and chimpanzees for their ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 43 publications
6
93
1
1
Order By: Relevance
“…Previous studies have shown that chimpanzees are willing to wait longer for rewards of increasing relative amount [22], but can exhibit similar levels of patience for different types of rewards when their amounts are constant (e.g. choosing to delay gratification for larger amounts of food, compared with delaying for the same quantities of tokens [23]). However, it is unknown if chimpanzees would exhibit greater patience when faced with decisions about minimally cooked foods compared with the same quantity of raw food.…”
Section: Experiments 2: Patience When Waiting For Cooked Foodmentioning
confidence: 99%
“…Previous studies have shown that chimpanzees are willing to wait longer for rewards of increasing relative amount [22], but can exhibit similar levels of patience for different types of rewards when their amounts are constant (e.g. choosing to delay gratification for larger amounts of food, compared with delaying for the same quantities of tokens [23]). However, it is unknown if chimpanzees would exhibit greater patience when faced with decisions about minimally cooked foods compared with the same quantity of raw food.…”
Section: Experiments 2: Patience When Waiting For Cooked Foodmentioning
confidence: 99%
“…Monkeys also chose the PVC objects more than the metallic ones. Although both metal and PVC are materials the monkeys frequently encounter (their housing and enrichment is made of both materials), the PVC tokens were more similar in form to experimental tokens used routinely in our lab (e.g., Brosnan et al, 2011;Evans et al, 2012), which may explain their preference. Unfortunately, this preference for PVC could mean that their preference for certain materials overrode any preference based on their partner's choice.…”
Section: Discussionmentioning
confidence: 98%
“…One female subject often chose not to participate (i.e., did not enter the testing area on more than half of the opportunities that she had to do so) and so was dropped from testing, resulting in a sample size of 10 individuals. Prior to this study, all of our subjects had participated in studies that involved exchanging objects with an experimenter (e.g., Brosnan et al, 2011;Evans, Beran, Paglieri, & Addessi, 2012). Subjects were always housed with their social groups except when they separated voluntarily for non-invasive behavioral and cognitive testing.…”
Section: Subjects and Housingmentioning
confidence: 99%
“…Monkeys show more variable performances on accumulation tasks and other delay of gratification tasks (e.g., Addessi et al, 2013;Anderson, Kuroshima, & Fujita, 2010;Evans & Beran, 2007b;Evans, Beran, Paglieri, & Addessi, 2012;Pel茅, Micheletta, Uhlrich, Thierry, & Dufour, 2011). Showing self-control through delay of gratification also can be incredibly difficult for humans, with failures in the form of overeating, smoking, drug use, and inadequate financial savings all leading to highly negative future outcomes.…”
Section: Dealing With Fallibility: Strategic Delay Of Gratificationmentioning
confidence: 99%